DEVELOPING SOFT SKILLS OF FUTURE PSYCHOLOGISTS IN THE EDUCATIONAL PROCESS (Psychology Travelogs, 2024)
In the professional environment, it is common to divide skills into two types: soft and hard skills. The former help to solve life challenges and interact with other people, while the latter help to achieve the best results in a particular profession. It is emphasized that soft skills are skills that each of us has, but not everyone has reached a high professional level.Soft skills help to solve life problems and work with other people. Not everything always goes smoothly, and a future psychologist must be able to cope with difficulties, take responsibility, and look for solutions. To do this, they need to be able to communicate, defend their ideas, think critically, and work in a team.It has been proven that if students do not have the desire to develop, it will be difficult to improve soft skills and change themselves. Though everyone possesses soft skills, they do not all reach the high level. The main success lies in getting feedback and analyzing the stage they have passed - without all this, it will be extremely difficult to move on.It has been found that customer focus, project management, mentoring, non-violent communication, decision-making, problem solving, emotional intelligence, learning ability, working under uncertainty, lean manufacturing, ecological thinking, self-reflection are effective methods of developing soft skills. The article describes the specifics of developing students’ soft skills who are future psychologists.
Keywords: developing; soft skills; future psychologists; educational process